Initiative and creativity of architecture students in participating in the gate design competition of PGRI University Yogyakarta - tio, tio syahada; Aulia, Amanda; Rossa, Ira; Kartika, Desi; Anto Buomonabot, Supriadi S Mille (Yayasan Putra Adi Dharma, 2024)
The land currently owned by UPY will be planned to be developed into lecture buildings and laboratory buildings, therefore a comprehensive design is needed to become UPY's Unit IV Campus. The initiative and creativity of architecture students in taking part in the gate design competition of PGRI University Yogyakarta can be explained as their encouragement to contribute significantly in shaping the visual identity of the campus. This desire arises as an effort to enrich the learning experience, improve design skills, and respond to real challenges in an academic environment.